The Effect of Product Quality, Brand Image, and Promotion on Sportwatch Purchase Intention Among Millennials - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Pusat Riset dan Inovasi Nasional, 2025)
The development of wearable technology such as sportwatches has driven an increase in purchasing interest, especially among millennials. This study aims to analyze the effect of product quality, brand image, and promotion on the purchase intention of sportwatches in the millennial consumer segment in Indonesia. This study uses a quantitative approach with an associative method. The sample consisted of 100 millennial respondents who were selected purposively, with an instrument in the form of a Likert scale closed questionnaire. Data were analyzed using multiple linear regression, F test, t test, and coefficient of determination. The results of the analysis show that the three independent variables, both simultaneously and partially, have a significant effect on the purchase intention of sportwatches. The product quality variable is the dominant factor in influencing purchase intention, followed by brand image and promotion. The coefficient of determination (Adjusted R Square) of 66.3% indicates that the combination of the three variables is able to explain most of the variation in consumer purchase intention. These findings provide strategic implications for manufacturers in designing a more adaptive marketing approach to millennial preferences that prioritize quality, brand reputation, and digital promotional interactions.